2004
DOI: 10.1007/s10654-004-2219-1
|View full text |Cite
|
Sign up to set email alerts
|

The consistency of shingles and its significance for health monitoring

Abstract: Accurate estimation of monitored populations is essential for epidemiological study. Many countries do not have systems of patient registration and routine disease surveillance is thereby hindered. We studied the incidence of shingles over time and investigated the hypothesis that the incidence is consistent and could be used as a proxy for estimating the monitored population. Annual incidence rates of shingles reported in the Weekly Returns Service (WRS) since 1970 and in the Dutch Sentinel Network (DSN) over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Increases in HZ incidence in the elderly population have been reported in several studies in countries with and without varicella vaccination programs (3, 16, 17, 19, 20, 40, 41); however, other studies have not shown an increase (32, 33). We have no explanation for the trend and expect that it awaits a better understanding of why a substantial minority of persons have HZ during their lifetime, whereas most do not.…”
Section: Discussionmentioning
confidence: 90%
“…Increases in HZ incidence in the elderly population have been reported in several studies in countries with and without varicella vaccination programs (3, 16, 17, 19, 20, 40, 41); however, other studies have not shown an increase (32, 33). We have no explanation for the trend and expect that it awaits a better understanding of why a substantial minority of persons have HZ during their lifetime, whereas most do not.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, incidence rates become a straightforward tally of all administrative codes in the desired age range or by gender specification. Several types of administrative data have been used for such incidence estimates: single-insurer populations such as those covered by large health maintenance organizations (4), provincial populations (12), or countrywide populations (4,5,8,10,13,22,23). Such populations are usually large and are selected because they have data in a uniform electronic format that makes it efficient and relatively inexpensive to search for billing codes for HZ care.…”
mentioning
confidence: 99%
“…We explore potential reasons for differences and estimate the impact of each method on future assessments of HZ incidence and complication rates in the post-HZ vaccine era (19,20,23,26,27).…”
mentioning
confidence: 99%
“…The highest risk of death is to the very young and very old (over 85 years) (Heininger and Seward, 2006). Fleming et al (2004) suggest that 99% of the population will be immune by the age of 40, so 99% of the adult population are at risk of developing shingles.…”
Section: Varicellamentioning
confidence: 99%
“…Wareham and Breuer (2007) suggested that the average general medical practice sees between three and fi ve cases of shingles per year. Fleming et al (2004) claimed that statistics for HZ over the past 30 years have remained constant for all ages, except for people over the age of 65, in whom there has been a gradual increase. There may be a link between ethnicity and shingles.…”
Section: Herpes Zostermentioning
confidence: 99%